2018
DOI: 10.1177/1053451218767901
|View full text |Cite
|
Sign up to set email alerts
|

A Six-Step Decision-Making Process to Guide Social Skills Instruction

Abstract: The availability of effective research-based interventions and practices within schools is a growing concern within the field of education. There remains a lack of interventions that have been fully evaluated for use within schools and by school personnel, particularly in the area of social skills interventions. Understanding the need for social skills interventions and the long-term impact of not receiving appropriate programming is clear. Less is established on how to define the specific need and appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Research indicates that the lifelong success of a child/youth is not only based on their academic achievement, but upon their ability to interact successfully with others in terms of interpersonal competencies (Grant et al, 2017;National Research Council [NRC], 2012). Because of the uniqueness of children/youth with disabilities, the appropriate approach to building a repertoire of skills focused on relating and interacting with other people is to teach social skills through direct and explicit instruction of the identified skill to enhance interactions in a variety of contexts (Lane et al, 2005;McGinnis, 2012;McGinnis et al, 2012;Stichter et al, 2019). While not specifically mentioning social skills, both the Every Student Succeeds Act (ESSA, 2015) and the U.S. Department of Education (DOE, 2014) Resource Guide provide support for evidence-based programming related to social and emotional learning focused on appropriate behavior within the school environment.…”
Section: Social Skills Within the School Environmentmentioning
confidence: 99%
“…Research indicates that the lifelong success of a child/youth is not only based on their academic achievement, but upon their ability to interact successfully with others in terms of interpersonal competencies (Grant et al, 2017;National Research Council [NRC], 2012). Because of the uniqueness of children/youth with disabilities, the appropriate approach to building a repertoire of skills focused on relating and interacting with other people is to teach social skills through direct and explicit instruction of the identified skill to enhance interactions in a variety of contexts (Lane et al, 2005;McGinnis, 2012;McGinnis et al, 2012;Stichter et al, 2019). While not specifically mentioning social skills, both the Every Student Succeeds Act (ESSA, 2015) and the U.S. Department of Education (DOE, 2014) Resource Guide provide support for evidence-based programming related to social and emotional learning focused on appropriate behavior within the school environment.…”
Section: Social Skills Within the School Environmentmentioning
confidence: 99%
“…Organizing decisions were viewed as efforts to program, coordinate, and implement-the total effort to make a plan operational. (Stichter et al, 2019) identified the following steps in the managerial decision-making processes: 1) Identify the decision to be made. As it is a must to identify the problem that needs to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Several aspects must be considered in making a decision, namely: (i) recognizing or determining a problem or issue; (ii) analyzing difficulties: problem classification, collecting data, and problem specifications; (iii) determining problem-solving criteria; (iv) developing an action plan or strategy; formulate alternatives, formulate the consequences of each alternative, choose an action plan; (v) develop an action plan, program communication and monitor as well as evaluation (Shrestha et al, 2019;Stichter et al, 2019). Decision-making is a combination of analysis and judgment, intuition, and the ability to utilize business by taking feelings (Nemtinov et al, 2019).…”
Section: Introductionmentioning
confidence: 99%